Familial Adenomatous Polyposis in Pediatric Patients: A Case Series - Rogalidou, Maria; Katsanos, Konstantinos; Batistatou, Anna; Tzoufi, Meropi; Christodoulou, Dimitrios; Siomou, Ekaterini (Archives of Clinical and Biomedical Research, 2025)
Background: Familial Adenomatous Polyposis (FAP) is a rare inherited disorder characterised by the development of hundreds to thousands of adenomatous polyps in the colon and rectum. It is caused by mutations in the APC (Adenomatous Polyposis Coli) gene located on chromosome 5q21. Without treatment, nearly all individuals with FAP will develop colorectal cancer, typically by the fourth decade of life. Case Series Presentation: We retrospectively analysed the clinical features of pediatric patients diagnosed with FAP at our centre. Seven patients, aged between 7.5 and 17 years (5 boys and 2 girls), were included in this case series. All patients had a positive family history of FAP. One patient was diagnosed with Turcot syndrome; the remaining six had no additional pathological findings or associated conditions. All patients were asymptomatic at presentation, with normal growth parameters and unremarkable routine blood tests. Genetic testing was performed in five patients, and all underwent endoscopic evaluation with histological examination. Various grades of dysplasia were identified in the colonic polyps. Management strategies were individualised for each patient based on the severity and extent of disease. Conclusions: Colorectal adenocarcinoma can develop in pediatric patients with FAP, even in the absence of symptoms. Children with a positive family history should undergo early and regular screening. In confirmed cases, close surveillance and timely intervention are essential to prevent malignant transformation.